2021
DOI: 10.1002/ctm2.352
|View full text |Cite
|
Sign up to set email alerts
|

AMD1 upregulates hepatocellular carcinoma cells stemness by FTO mediated mRNA demethylation

Abstract: AMD1 could stabilize the interaction of IQGAP1 with FTO. The interaction with IQGAP1 increases FTO phosphorylation and expression. High level of FTO promotes pluripotency factors expression and elevates stem cell-like property of HCC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 67 publications
0
41
0
1
Order By: Relevance
“…Although it is reported that m6A modification is involved in different biological and pathological processes [ 18 ], the underlying mechanisms of m6A that participated in PCa progression remain largely unknown. Our results suggested an unusual tumor suppressor role in PCa, which is known as an oncogene in other types of tumors [ 19 21 ]. We demonstrated that FTO is downregulated in prostate adenocarcinoma, and the downregulation of FTO was negatively correlated with disease-free survival.…”
Section: Discussionmentioning
confidence: 62%
“…Although it is reported that m6A modification is involved in different biological and pathological processes [ 18 ], the underlying mechanisms of m6A that participated in PCa progression remain largely unknown. Our results suggested an unusual tumor suppressor role in PCa, which is known as an oncogene in other types of tumors [ 19 21 ]. We demonstrated that FTO is downregulated in prostate adenocarcinoma, and the downregulation of FTO was negatively correlated with disease-free survival.…”
Section: Discussionmentioning
confidence: 62%
“…METTL3 and METTL14 can regulate the progression of multiple types of cancer, including bladder cancer [ 15 , 16 ], gastric cancer [ 17 , 18 ], cervical cancer [ 19 ], hepatocellular carcinoma [ 14 , 20 ], and pancreatic cancer [ 21 ]. FTO plays a central role in oral squamous cell carcinoma [ 22 ], hepatocellular carcinoma [ 23 ], bladder cancer [ 24 ], and acute myeloid leukemia [ 9 , 25 ]. Although studies have also demonstrated that m6A modification plays a key role in CRC [ 4 , 12 ], the function and regulatory mechanism of m6A in CRC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…YTHDF1 expression, mediated by HIF-1α, supports that hypoxic stress might lead to the alteration of cancer epigenetics, such as the translation of m6A-modified oncogenic mRNAs, to facilitate HCC malignancy. A recent study corroborated that AMD1 expression is the independent factor for overall survival (OS) and disease-free survival (DFS) in HCC ( Bian et al, 2021 ). Several investigations found high expression of AMD1 in HCC tissue and showed that AMD1 regulates the expression of NANOG, SOX2, and KLF4, which are involved in HCC initiation, metastasis, and chemoresistance.…”
Section: Mechanism Of Rna Methylation In Hccmentioning
confidence: 81%